ETHICS IN RADIOLOGICAL PROTECTION FOR MEDICAL DIAGNOSIS AND TREATMENT (Annals of the ICRP, 2024)
Publication 138 defines the ethical foundations of the ICRP System of Radiological Protection based on core values (beneficence and non-maleficence, dignity, justice, and prudence) and procedural values (accountability, transparency, and inclusiveness). The purpose of the present publication is to propose a practical application of values for medical radiological protection professions. As medicine has a long history and strong culture of ethics, this publication starts by identifying the shared values, and defines a common language between biomedical ethics and radiological protection. The core values are very similar, with the autonomy of biomedical ethics, which can be seen as a corollary of dignity, and the precautionary principle, which can be understood as the implementation of prudence. In recent years, medical education and training has emphasised the values of solidarity, honesty, and, above all, empathy. All these values are defined and interpreted in the specific context of the use of ionising radiation in medicine. For those more familiar with radiological protection, the ethical implications of their actions are described. Conversely, for those who already have a good background in ethics, this publication highlights the specificities of ionising radiation that also deserve consideration. In order to emphasise the coherence between the values involved in biomedical ethics and those involved in radiological protection, this publication proposes to combine them: dignity and autonomy; beneficence and non-maleficence; prudence and precaution; justice and solidarity; transparency, accountability, and honesty; and inclusiveness and empathy. This allows a structured review of practical situations from an ethical perspective. For the sake of both example and education, this publication proposes 21 realistic scenarios (11 in imaging procedures and 10 in radiation therapies). Sensitising questions are provided to stimulate reflection and discussion. The ultimate goal is to be able to use ethical values in clinical imaging and therapy situations. Required education and training in ethics is essential for medical radiological workers throughout their career span. An example of a framework of knowledge, skills, and competencies is proposed. In order to assist the reader in a theoretically complex subject, key messages are distributed throughout the text as fixed points that can be easily understood. Although primarily aimed at medical radiological protection professionals, this publication is also intended for authorities, patients, and the public. © 2024 ICRP. Published by SAGE.